Accuracy Evaluation of Real-Time GNSS Precision Positioning with RTX Trimble Technology = Ocena dokładności precyzyjnego pozycjonowania GNSS w czasie rzeczywistym z wykorzystaniem technologii RTX Trimble - Ochałek, Agnieszka; Niewiem, Witold; Puniach, Edyta; Ćwiąkała, Paweł (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In this paper, authors present results of accuracy verification of the Trimble RTX technology. The GNSS receiver Spectra Precision SP60 was used in Cyprus (Kato Paphos Archaeological Park). To evaluate the accuracy of the receiver, two measuring test networks (consisting of 30 and 55 control points) were established.
Keywords: Global Navigation Satellite System; data processing; statistical analysis; real-time systems; GNSS; przetwarzanie danych; analiza statystyczna; system czasu rzeczywistego